BENIH-BENIH IDEOLOGI ISLAMISME RADIKAL DI KALANGAN SEJUMLAH MAHASISWA NTT - Bernardus Raho; Mathias Daven; Hendrikus Maku (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This article focuses on the roots of radicalism as can be seen in young Muslims in NTT Province. The majority of the population of this province are either Protestant or Catholic Christians. Nationally, NTT has a reputation for being a province which is coloured by religious tolerance. People of different religions live side by side peacefully. A probable reason for this is the fact that family and friendship relationships tend to cross religious boundaries. However, in recent times religious harmony has been impacted by radical thinking among tertiary Muslim students. These seeds can be seen in their understanding of, and attitude to, radical Islamism. At the level of understanding, they do not differentiate between Islam as a religion and Islam as an ideology. At times they identify radical Islamism as the teaching of Islam. Attitude-wise, this article points out that a considerable number of respondents hold certain convictions which are in line with the ideology of radical Islamism. Keywords: Radical Islamism, fundamentalism, radical Islam, Islamic student, ideology of a Islam, terror, terrorism.